The new proposed circumstances of Fathers and sons in Sao Paulo the translation of Stanislavski's originary poetics in national context - Vieira Romano, Lucia Regina [UNESP] (Univ Sao Paulo, Escola Comunicacoes & Artes, 2016)
For us to think about Stanislavski's legacy and his poetics of acting in national context, I propose a dialogue with the experience of the production of Fathers and Sons, directed by Adolf Shapiro in Sao Paulo. Inspired by the creative encounter between mundana companhia and Shapiro (and by him, with the theatrical tradition drawn by Stanislavski), I intend - borrowing terms from the anthropological approach - to relate the experience of Brazilian actors and actresses working with the system to a process of interculturation of traditions and techniques, to reflect on the implications of geographical horizons and historical and temporal boundaries for the transformation of the original acting matrices.
Keywords: Theory of acting; Contemporary theater; Interculturalism; Stanislavski system